SCIENTIFIC AND PEDAGOGICAL EXPRESSION OF THE COMPONENTS OF INDEPENDENT CREATIVE ACTIVITY IN THE TECHNOLOGY OF PAINTING - Toxirova Rayxona Toxirjon qizi (Western European Studies, 2025)
This article provides a detailed explanation of the content, components, and scientific-pedagogical foundations of independent creative activity in the process of painting technology. Independent creativity, as a central factor in painting education, plays an important pedagogical role in developing the student’s observation skills, artistic perception, imagination, technical mastery, compositional thinking, the ability to define artistic problems, and reflective skills. The article analyzes the theoretical and practical aspects of independent creative processes and the specific characteristics of working with artistic means such as color, light– shadow, texture, and composition. In addition, the role of modern interactive methods, studiobased approaches, and plein-air practices in developing independent creative activity is discussed. The findings show that independent creativity is a highly significant pedagogical mechanism for developing a student’s artistic thinking, aesthetic worldview, and integrative artistic competence in painting technology
Keywords: independent creative activity; painting technology